The Significance of Entrepreneurial Intentions for the Silversmith Businesses Sustainability in Kamasan Village, Klungkung-Bali - Ida Ketut Kusumawijaya; Partiwi Dwi Astuti (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
Silver crafts in Kamasan Village as a creative business are embedded in people's lives, becoming a daily economic activity in the community, especially silversmith in Kamasan Village, Klungkung District, Klungkung Regency, Bali Province. The business activities of silversmith in Kamasan Village are part of the microeconomic structure to encourage the growth of the community's creative economy with unique crafts as a competitive advantage for a sustainable future. However, on the other hand, silversmith businesses in Kamasan Village face many obstacles, namely: limited business capital, low mastery of technology and science, inadequate business management and the absence of entrepreneurial intention among craftsmen. The aims of this community service are to raise awareness of the importance of entrepreneurial intention for the silversmith community in Kamasan Village, Klungkung District, Klungkung Regency, Bali Province for business sustainability. The methods of theses community service are a participatory action research approach oriented towards empowering and developing the entrepreneurial intention of silversmith in Kamasan Village. Results of theses community service are silversmith in Kamasan Village, Klungkung District, Klungkung Regency, Bali Province. First, there is an increase in knowledge from silversmith in Kamasan Village regarding the importance of entrepreneurial intention to be able to continue their business by creating a career goal to become a sustainable entrepreneur who will promote sustainable development and will favor social goods and economic gains. Second, the knowledge of silversmith in Kamasan Village has increased in understanding practices and decision-making activities principally through entrepreneurial attitude, subjective norms and perceived behavior control. Silversmith in Kamasan Village have knowledge of the significance of entrepreneurial intention as a science that is applied by developing creativity to realize superior performance. Third, silversmith in Kamasan Village agreed to strengthen their competitiveness to maintain their business by fostering entrepreneurial intention. For silversmiths in Kamasan Village, entrepreneurial intention is a driving force for organizing, managing, solving problems and developing and maintaining the business.